TRANSTORNO DO ESPECTRO AUTISTA E ISOLAMENTO SOCIAL NA PANDEMIA DA COVID 19: um estudo de caso nas ações da ONG’MIM no município de Breves - Marajó - COSTA, Fatima Indira de Oliveira (2024)
The main focus of this article is to analyze the results of studies and perceptions arising from the mapping carried out by the NGO Movimento pela Inclusão no Marajó – MIM with families of people with Autism Spectrum Disorder, with a view to investigating whether public policies are managing to reach people with ASD and their families in the municipality of Breves, making a cut in the educational scope. The problem that guided the research was: What impacts did the Covid-19 pandemic have on the educational scope of children with Autism Spectrum Disorder – ASD, in the municipality of Breves? This is a research with a qualitative approach supported by bibliographic research, of the Case Study type, in which the mapping carried out by the NGO MIM with the families of people with ASD in the municipality was used as data and information collection instruments. Regarding the analysis and interpretation of data and information, the principles of content analysis were used. Vieira et al. were used as a theoretical basis. (2020), Brasil (1994), Dias, Santos and Abreu (2021), Nazari (2017), Mantoan (2006) among others. The results indicate that the academic perspectives on the topic in question are incipient and that there is a need for a clearer understanding of the intricacies of the school inclusion process and effective policies for people with ASD in the municipality of BREVES, it also points out that families need greater participation in this inclusion process, it is necessary to use methodological strategies that work on the basic educational needs of these students in this pandemic period that has brought so many transformations.